Growth kinetics and production of glucose oxidase using Aspergillus niger NRRL 326 - Gera, N. (Array, 2008)
Summary: In this paper, we demonstrate the substrate inhibition phenomena for growth kinetics of Aspergillus niger NRRL 326 grown on sucrose during glucose oxidase production. The initial set of experiments were carried out using three different substrates, viz., glucose, sucrose and raffinose of which it was observed that sucrose serves better for higher production of glucose oxidase. Experiments involving sensitivity studies conveyed that substrate inhibition became predominant when sucrose mass concentration was above γ = 30 g L-1 in the cultivation medium. The later part of the work was dovetailed towards validation of substrate inhibited growth kinetics with established models such as Haldane, Andrews, Luong, Han-Levenspiel and Aiba. Finally, it was observed that none of the classical models explains the kinetics well